Role of Head Position in Stroke Outcome: An Observational Study from Tertiary Care Hospital in Pakistan - Husnain Hashim, Danial Bajwa, Laraib Shahid, Maroosha Khan, Fariha Irfan, Saeed Arif (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Acute ischemic stroke patients mainly rely on cerebral blood flow (CBF) to sustain penumbral tissue perfusion in turn depend on arterial blood pressure in affected cerebral autoregulation. Head positioning either sitting-up or lying flat allows gravitational force to enhance leptomeningeal circulation and collateral blood flow. The present study aimed to determine the role of head position in acute ischemic stroke patients. Methodology: This prospective observational study was conducted on 500 stroke patients in the Department of Neurology and Medical department of Fauji Foundation Hospital, Rawalpindi from January 2020 to December 2021. Patients with acute ischemic stroke receive care in either a lying flat on bed or sitting-up position with elevated head position at 30 to 45 degrees. The designated position was established shortly after hospital admission and was held for 24 hours. Outcomes such as pneumonia, aspiration pneumonia, and increased hospital stay, disability, and mortality were associated with flat head position and elevated head position. Modified Rankine scale (0-6) was used for assessing the degree of disability as a primary outcome in three months. Rankine scale higher score indicates the greater disability and maximum score 6 indicate mortality. Results: The average time from initiation of assigned position and onset of ischemic stroke symptoms was 14 hours (IQR 5-35). Patients in the sitting position group (93%, p<0.001) were more likely than the lying-flat group (82%, p<0.001) in maintaining their position for 24 hours. Based on a modified Rankine scale, both lying flat and sitting-up position groups had no significant differences in a proportional-odds model in terms of 90-days disability outcomes distribution. The mortality rate in lying flat and sitting-up position was 6.8% and 6.9% (p=0.79). Also, both groups had no significant differences in terms of severe outcomes including pneumonia. Conclusion: The present study found that disability outcomes in acute stroke patients were similar irrespective of their position either flat or sitting position with head elevated at 30 to 45 degree for 24 hours. The prevalence of AIS was 95.6%. Keywords: Head position, Acute ischemic stroke, Outcomes